2019
DOI: 10.15586/jptcp.v26i2.601
|View full text |Cite
|
Sign up to set email alerts
|

Is Body Fat Percentage a Good Predictor of Menstrual Recovery in Females With Anorexia Nervosa After Weight Restoration? A Systematic Review and Exploratory and Selective Meta-Analysis

Abstract: The resumption of menses (ROM) is an important outcome in anorexia nervosa treatment and is considered as a sign of recovery. Identification of relevant factors in its prediction is important in clinical practice. Therefore we aimed to conduct a systematic review and exploratory meta-analysis of the association between total body fat percentage (%BF) and ROM after weight restoration in adolescents and young adults with anorexia nervosa. The study was conducted by adhering to Preferred Reporting Items for Syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…The resumption of menstruation is one of several important outcome measures in female AN treatment and body fat plays an important role. Traboulsi et al [18] suggest there is a cut-off point of 21% total body fat needed to resume menstrual cycle and, in line with Lackner et al [13], they suggest that assessing body composition in all patients with AN as a diagnostic criteria as well as in treatment protocols, could guide the treatment team in offering an individual treatment plan. We found, in this limited number of subjects, a conjecture that both body fat and energy intake might be necessary conditions to ensure menstruation and, in our study, mean body fat percent in menstruating women was 27% (17e41%) and in the amenorrhoeic group body fat percent was 20% (9e32%).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The resumption of menstruation is one of several important outcome measures in female AN treatment and body fat plays an important role. Traboulsi et al [18] suggest there is a cut-off point of 21% total body fat needed to resume menstrual cycle and, in line with Lackner et al [13], they suggest that assessing body composition in all patients with AN as a diagnostic criteria as well as in treatment protocols, could guide the treatment team in offering an individual treatment plan. We found, in this limited number of subjects, a conjecture that both body fat and energy intake might be necessary conditions to ensure menstruation and, in our study, mean body fat percent in menstruating women was 27% (17e41%) and in the amenorrhoeic group body fat percent was 20% (9e32%).…”
Section: Discussionmentioning
confidence: 89%
“…El Ghoch et al [17] described how a higher total body fat percentage at inpatient discharge is associated with the resumption of menstruations at 1-year follow-up in weightrestored adult females with AN. Traboulsi et al [18] have recently shown that patients with AN who resumed their menstrual cycle, had a significantly higher mean body fat percentage compared to those who did not. Body fat percentage was an independent predictor of the resumption of menstruations in this population, and an increase of only one percentage point of body fat increased the odds of menstruation by 15e20%.…”
Section: Introductionmentioning
confidence: 99%
“…These results extend the understanding about estrogenic actions on feeding regulations, which could be bidirectional depending on the internal energy state and contribute to the maintenance of energy homeostasis in face of various environmental challenges. Although E2 levels and the expression of ERα in the hypothalamus may not undergo dynamic changes during the fasting–feeding transition in normal females [ 71 ], our finding that E2 and ERα signals are required for female animals to properly respond to hunger provided new mechanistic insights on the association of abnormal feeding behavior with irregular estrogen levels in certain medical conditions that disproportionally affect women, such as anorexia nervosa [ [72] , [73] , [74] ], and therefore may facilitate the development of suitable therapeutic strategies for these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…testosterone in men and oestrogens in women) secretion [48], also known as the hypothalamus-pituitary-gonadal (HPG) axis. Thus, it could be speculated from the human studies that leptin and kisspeptin act in concert to affect puberty and reproduction, and lower leptin contributes to the reduced kisspeptin levels and GnRH secretion, leading to lower testosterone and oestrogen secretion in fasting males and AN females, respectively [49,50].…”
Section: Endocrine Disruption In Anmentioning
confidence: 99%
“…Oestrogen was also inversely associated with fat attenuation in both sWAT and vWAT in AN females [ 31 ]. Chronically reduced synthesis of oestrogen causes amenorrhoea in female AN patients, and resumption of menses is considered to be a biological indicator of health status after weight restoration, which is associated with a higher percentage of body fat mass [ 50 ]. Interestingly, plasma kisspeptin is positively correlated with BMI and body fat mass in premenopausal adult females with AN [ 49 ] while inversely correlated with BMI in adolescent girls [ 55 ], indicating different regulatory patterns of HPG axis activation in adolescent and adult females in the AN state.…”
Section: Endocrine Disruption In Anmentioning
confidence: 99%